In India, Ten Krishi Vigyan Kendras (agriculture extension offices) in two Indian States are setting up Farming System for Nutrition models - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Wardha district, Maharashtra, India was one of the sites of a research study by the Leveraging Agriculture for Nutrition in South Asia (LANSA) partnership to demonstrate the feasibility of a farming systems approach to address the problem of undernutrition. The endline survey in 2017 showed evidence of improvement in dietary diversity. Farmers have emerged as spokespeople and shared their experience at block and district level forums. Farmers from another 16 villages have been motivated to practise similar interventions.